Pulmonary mucormycosis following autologous hematopoietic stem cell transplantation for rapidly progressive diffuse cutaneous systemic sclerosis: A case report. Issue 31 (31st July 2020) - Boumaza, Xavier; Lelièvre, Lucie; Guenounou, Sarah; Borel, Cécile; Huynh, Anne; Beziat, Guillaume; Delavigne, Karen; Guinault, Damien; Garric, Marie; Piel-Julian, Marie; Paricaud, Kim; Moulis, Guillaume; et al.
Abstract: Rationale: The use of autologous hematopoietic stem cell transplantation (AHSCT) for autoimmune diseases has become the first indication for transplant in nonmalignant disease. Mucormycosis is a rare invasive infection with increasing incidence in patients treated with AHSCT. We report the first case of pulmonary mucormycosis following AHSCT for systemic sclerosis (SSc). Patient concerns: A 24-year-old woman with rapidly progressive diffuse cutaneous SSc presented with an acute respiratory distress syndrome 6 days after AHSCT. Diagnoses: The results of clinical and computed tomography scan were consistent with pulmonary mucormycosis and the diagnosis was confirmed by a positive Mucorales Polymerase Chain Reaction on a peripheral blood sample. Interventions and Outcomes: Early antifungal therapy by intravenous amphotericin B provided rapid improvement within 4 days and sustained recovery after 2 years of follow-up. Lessons: With the progressively increasing use of AHSCT and other stem cell therapy for treatment of severe SSc and other autoimmune diseases, the potential onset of rare post-transplant fungal infections, such as mucormycosis, requires careful patient monitoring and better awareness of early initiation of adequate therapy.